When tomorrow is yesterday : Black Theology, Black Consciousness, and our incomplete revolution - Boesak, Allan (Stellenbosch Theological Journal, 2021)
In an early 1977 interview, Steve Biko offered not only insights into the events of June 16 the year before, but also a prophetic analysis of a post-apartheid situation if black people's political liberation did not include economic liberation as an essential and indispensable reality. Taking those insights as point of departure, and engaging the intellectual work of Kwame Nkrumah, this article argues that Biko's words were not only prophetic and correct, but absolutely relevant for South Africa's neo-colonial situation today. Embracing the thinking of Iranian social scientist Hamid Dabashi, I further contend that the events on June 16, 1976 were the start of a revolution, in the sense of "delayed defiance", still ongoing and manifesting itself in different forms in South Africa today. An analysis of our present South African context, especially as regards the plight of the poor, women, the LGBTQI community, and the still-contested state of our reconciliation process as illustrated by the controversies stirred by former president De Klerk's denialism regarding apartheid, leads me to conclude that this revolution is "incomplete".